Aromatherapy Candle Making Training from Coffee Mixture in Kutorembet Village, Lebakbarang District, Pekalongan Regency - Muhammad Umar Chasani; Awali, Husni; Assyfa Nanda Hersa; Asti Fanani; Ayu Hartati; Tia Septiani (Amaluna: Jurnal Pengabdian Masyarakat, 2024)
Training on Making Aromatherapy Candles from Coffee Mixtures. This article discusses the process of making innovative aromatherapy candles using coffee as the main ingredient. By utilizing coffee as a source of warm, refreshing aroma, this candle making technique combines natural and additional ingredients to create a product that not only provides a pleasant fragrance, but also relaxing benefits. This article discusses the detailed steps, ingredient composition, and benefits of coffee-based aromatherapy candles in creating a calm and comfortable atmosphere at home